Development of EPPT1 targeted biocompatible drug delivery system and investigation of its anticancer activity - Karaca, Ezgi (İstanbul Medipol Üniversitesi Fen Bilimleri Enstitüsü, 2020)
Recently, the superior properties of graphene to other biomaterials have made graphene an indispensable and unique material for anticancer drug delivery research, gene and peptide transport. On the other hand, the undeniable beneficial effects of graphene provided by a wide surface area could be limited by toxic effects. Oxidized formation of graphene (G) is a graphene oxide (GO) that comprises a lot of oxygen functional groups which make it hydrophilic. Unfortunately, despite GO with an excellent functionalization ability and good solubility in water conditions, defected areas hamper sp3 hybridized carbon surface area. Partially reduction of some oxygen functionality on GO generates reduced graphene oxide (rGO) with less solubility but better graphene properties. Therefore, reduced graphene oxide is chosen due to a wider surface area and less toxicity associated with functional groups for several biological applications. Covering the wide surface area of rGO is a common strategy to have better water solubility and biocompatibility. Poly(ethylene glycol) is a commonly used polymer that provides an ability to nanoparticle prolonged circulation time with covering the unknown nanomaterial from immune cells and decreases the uptake by the spleen and liver-resident phagocyte. This thesis study focuses on the development of an EPPT1 targeted, biocompatible graphene-based drug delivery system that can address the biocompatibility problem of rGO and show the potential of selective drug delivery into the target cell. The surface of the graphene oxide was coated with a functional copolymer poly[(ethylene glycol methacrylate)-co-(methyl methacrylate)-co-(1-pyrene methacrylate)-co-(3-azido propyl methacrylate)] P[PEGMA-co-MMA-co-PMA-co-AzPMA] that enhances the biocompatibility and water dispersibility via its PEG brushes. The copolymer also contains the multiple pyrene units to enhance the ?-? interactions with graphene surface and azide groups to do further targeting agent functionalization of the coated surface which ensures the recognition of uMUC1 receptors that is highly expressed on the membrane of breast cancer cells. Doxorubicin (Dox) as anticancer drug loading and releasing profile of the targeted, biocompatible graphene platform were deeply investigated by showing the effect of PEG brush length (500 g/mol and 2000 g/mol), the effect of having ionic azide groups on the surface, the effect of the order of drug loading and targeting agent conjugation on drug release rate. Anticancer activity was tested in two different breast-cancer cells of MCF-7 and MDA-MB-231 using MTS and Resazurin Assay. Once the drug release profiles of the carriers with the 95% drug loading capacity were investigated at acidic (pH:5.5) and the physiological conditions (pH:7.4), the results showed that longer PEG brushes slow down the drug release however it ensures the biocompatibility and aqueous medium solubility. Azide group containing carrier has a faster drug release profile because of the ionic interaction between positively charged Doxorubicin at acidic pH. EPPT1 peptide showed the charge balancing effect and slowed down the release even in the azide group containing carriers in both PEG brush molecular weights (500, 2000 g/mol). After the investigation of the drug release profile of the nanocarriers system in a different copolymer and synthesis order variety, in-vitro experiments have been done. MTS and Resazurin assay have been performed with the empty carrier, non-targeted, and targeted Dox loaded carriers with negative and positive controls on MCF-7 and MDA-MB-231 breast cancer fibroblast secondary cell lines. Resazurin has chosen as the most reliable assay to work with Dox loaded therapeutics. The results showed that 7.5 ?g/ml targeted, Dox loaded, PAMP coated rGO nanocarrier with PEG2000 brushes gives 24 % cell viability, while free Dox gives 25 % cell viability after 48h interaction with MDA-MB231 cells. Finally, the selective cellular uptake ability of the compositions was investigated qualitatively and quantitively by confocal microscopy and flow cytometry analysis and it is shown that EPPT1 targeted a graphene-based drug delivery system selectively can accumulate more into breast cancer cell lines.

Son zamanlarda grafenin (G) diğer biyomalzemelere göre üstün öözellikleri onu antikanser ilaç taşıma sistemi, gen ve peptit taşınmasında önemli bir material haline getirmiştir. Bir diğer yandan toksit etkileri kullanımı sınırlandırabilir. Grafen oksit (GO) onu hidrofilik yapan çok sayıda fonksiyonel oksijen grubu bulundurur. Fakat GO`in sahip oldu sp3 hibridize karbonları sebebiyle kusurlu yüzey oluşumu bulunmaktadır. GO üzerindeki oksijen grubunun azaltılmasıyla bu problem ortadan kalkabilir fakat çözünürlüğü kısmen azalır. Bunun için indirgenmiş grafen oksit (rGO) yapısı GO'in oksijence zengin gruplarının indirgenmesiyle elde edilir. rGO daha düzgün ve geniş yüzey alanı ve daha az toksisiteye neden olması rGO'yu biyolojik uygulamalar için daha cazip kılar. Fakat suda çözünürlüğünün ve biyouyumluluğunun düşük olması aşılması gereken bir sorundur ve bunun için genellikle yüzey kaplama stratejileri takip edilir. Poli(etilen glikol) (PEG) yüzey alanı kaplaması için kullanılan polimerlerden olup, kaplandığı nanoparçacığın kandaki dolaşım süresini uzatır ve immün hücreler tarafından karaciğer ve dalaktan atılımını engeller. Bu tez çalımasında, EPPT1 peptidiyle hedefli hale getirilmiş, rGO'nun biyouyumluluğunun iyileştirildiği grafen bazlı bir ilaç taşıma sisteminin geliştirimesi çalışılmıştır. Grafen oksidin yüzeyi indirgenirken poli [(etilen glikol metakrilat)-ko- (metil metakrilat)-ko-(1-pirenmetakrilat) -ko-(3-azido propil metakrilat)] P[PEGMA-co-MMA-co-PMA-co-AzPMA]'nın ?-? etkileşimiyle yüzeye kaplanmasıyla biyouyumluluk arttırılıp, fonksiyonlanabilir hale getirilmiştir. Hedefleyici ajan EPPT1 peptidi grafen yüzeyinin sahip olduğu azit gruplarına click reaksıyonu kullanılarak aşılanmıştır. Kanser hücrelerin hücre zarında yüksek orandaki varlığı bilinen reseptorlerden olan uMUC1 reseptorünü tanıyan peptit konjugasyonuyla grafen tabanlı ilaç tasıma sistemi hedefli hale getirilmiştir. Hedeflenen biyouyumlu nanoplatform kaplanan kopolimerdeki PEG gruplarının uzunluğu (500 g/mol ve 2000 g/mol) ve iyonik azit gruplarının varlığının ilaş yükleme ve salım davranışına etkileri ayrıntılı olarak incelenmiştir. Ayrıca, ilacın kompozisyona yüklenme sırası ve yüzeyde hedefleyici ajanın varlığının ilaç salım davranışı üzerine etki ettiği gözlenmiştir. % 95'e kadar ilaç yükleme kapasitesine sahip sistemin asidik (pH:5.5 ) ve nötr (pH:7.4) ortamlarda ilaç salım profilleri ortaya koyulmuştur. Elde edilen taşıyıcıların antikanser aktivitesi, MTS ve Resazurin testleri kullanılarak MCF-7 ve MDA-MB-231 meme kanseri hücrelerinde test edildi. Bunun sonucunda daha uzun PEG'li kopolimerleri ilaç salımının yavaşlamasına ancak biyouyumluluğun ve çözünürlüğün artmasına sebep olduğu, azit grubu içeren kompozisyonların Doxorubisin (Dox) ilacıyla arasındaki iyonik etkileşim daha hızlı bir ilaç salım profili oluşturduğu, hedefleyici peptide EPPT1 konjugasyonu sonrası kompozisyonlarda her iki PEG uzunluğunda (500 g/mol ve 2000 g/ mol) yük dengeliyici etki gösterdiği ve ilaç salımını yavaşlattığı gibi etkiler gözlenmiştir. İlaç salım profilleri de belirlenen farklı kompozisyonalarla in-vitro deneyler yapılarak, MTS, Resazurin testi meme fibroblast sekonder hücre hatlarında (MCF-7 ve MDA-MB-231) negatif kontrol, pozitif kontrol, boş taşıyıcı, hedefli ilaçsız ve hedefli Dox yüklü taşıyıcılar test edilmiştir. Sonuçlar ışığında Dox'un dalga boyu sebebiyle Resazurin testi en güvenilir test olarak seçilmiştir. PEG2000 içeren kompozisyonlar için 7.5 ?g/ ml Dox içeren hedeflenmiş rGO nanotaşıyıcılarla etkileşmiş hücrelerin 48 saat sonrasında yalnızca % 24 oranında canlı kalabildiği aynı koşullarda Dox ile muamele edilen hücrelerin ise % 25'inin canlı kaldığını gözlemlenmiştir.. Son olarak kompozsiyonların seçici olarak hücreye giriş kabiliyetlerini gözlemlenmek amacıyla eş odaklı mikroskopi ve akış sitometrisi ile nitel ve nicel olarak kanser hücrelerindeki etkinliği gözlemlenmiştir. Bunların sonucunda EPPT1 peptit içeren taşıyıcıların seçici olarak diğerlerine göre hücre içinde birikiminin fazla olduğu kanıtlanmıştır.
EPPT1 peptidi ile hedeflenmiş biyouyumlu ilaç taşıma sisteminin geliştirilmesi ve antikanser etkilerinin incelenmesi
Keywords: Graphene Oxide; PEG; ?-? Interaction; Doxorubicin; Biocompatible; Targeting; Drug Delivery System; Nanocarrier; Grafen Oksit; PEG; Pi-Pi Etkileşimi; Doksorubisin; Hedefleme; Nanotaşıyıcı